Aditivos em suplementos para bovinos de corte em pastejo - Naves, Karine Ribeiro dos Santos (2022)
The use of additives in protein-energy supplement on consumption, digestibility, and ruminal parameters of beef cattle in the growing phase was evaluated. Five male cattle were distributed in a 5x5 Latin square design. The animals were maintained under continuous grazing in individual paddocks of Urochloa brizantha cv. Marandu. The treatments consisted of mineral mixture (0.080 kg/animal.day), protein-energy supplement (PE) (4.0 kg/animal.day), PE with sodium monensin (120 mg/animal.day), PE with functional oil (2,500 mg/animal.day) and PE with active yeast (4,000 mg/animal.day). PE supplementation increased the intake of total dry matter (TDM), crude protein (CP), organic matter (OM), neutral detergent fiber corrected for ash and protein (NDFap) and digestible organic matter (DOM) in relation to the mineral mixture. There was no effect of the use of additives on nutrient intake and digestibility. However, PE supplementation increased the digestibility of DM, OM, CP, NDFap and DOM compared to the mineral mixture. PE supplementation increased ruminal ammonia nitrogen and serum urea nitrogen concentrations compared to mineral supplementation. And there was no effect of the use of additives on nitrogen metabolism and utilization. It is concluded that the use of monensin, functional oil and active yeast in a protein-energy supplement does not improve the nutritional parameters of beef cattle in the growing phase under the conditions of this study.